Early Postoperative Endoscopy for Evaluation of the Anastomosis after Esophageal Reconstruction - Lin, Tzu-Hsin; Huang, Pei-Ming (The Thoracic and Cardiovascular Surgeon, 2018)
Background Anastomotic leaks significantly affect hospital stay after esophageal surgery. Here, we investigated the efficacy of early endoscopy for predicting anastomotic healing and leaks after esophageal reconstruction.Methods A total of 65 consecutive esophageal cancer patients treated by cervical esophagogastrostomy underwent routine endoscopy between postoperative days 5 and 7. The anastomosis was scored for the degree of ischemia, stenosis, and torsion of the anastomotic axis. Independent associations between ischemia, stenosis, and torsion of the proximal esophagus and the risk of the anastomotic leak were examined using Spearman's rank correlation method.Results Assessment of the degree of mucosal ischemia in 65 patients shows well healing in 35, patch ischemia in 20, diffuse ischemia in 10, no necrosis in any patient. Stenosis was classified as 0 to 10% in 40 patients, 11 to 20% in 12, 21 to 80% in 11, and 81 to 100% in 2. The degree of torsion of the anastomotic axis was classified as 0 to 10 degrees in 52 patients, 11 to 90 degrees in 8, and 91 to 180 degrees in 5. With rising endoscopy scores, there was an increase in risk for leaks (score > 4.5, sensitivity 100%, and specificity 83.8%).Conclusions Early postoperative endoscopy facilitates the management of esophagogastrostomy anastomosis to predict leaks.
Keywords: endoscopy; esophageal reconstruction; anastomosis